Urgensi pengendalian internal terhadap efisiensi kinerja keuangan bank syariah - Fitrohcahya, Rahmadani Aidil (Maliki Interdisciplinary Journal, 2024)
This article discusses the urgency of internal control over the efficiency of Islamic banks’ financial performance with a focus on operations in accordance with sharia principles. This study aims to ensure that Islamic Banks operate with high integrity and policies that are in accordance with sharia principles. Through an analysis of the effect of internal audit and internal control on fraud prevention at Bank Syariah Indonesia, this study highlights the importance of internal control in maintaining the bank’s reputation and ensuring compliance with sharia principles. The results of this study are expected to provide new insights for financial, business, and banking practitioners in understanding the urgency of internal control in improving the efficiency of Islamic Bank financial performance.